2018
DOI: 10.1016/j.jiph.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Health care-associated infections in pre-transplant liver intensive care unit: Perspectives and challenges

Abstract: High HAI rate among ESLD patients is a matter of worry. Effective surveillance program, active infection control measures and national antibiotic policies are necessary to reduce the burden of HAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The increased risk of post‐transplant infection in those with pre‐transplant infection may be partially explained by shared risk factors. Infections during both periods were associated with longer pre‐transplant length of stay, and duration of hospitalization is a known risk factor to infection in both before and after liver transplant . However, pre‐transplant infection remained a significant risk factor for post‐transplant infection even when controlling for other confounding variables.…”
Section: Discussionmentioning
confidence: 91%
“…The increased risk of post‐transplant infection in those with pre‐transplant infection may be partially explained by shared risk factors. Infections during both periods were associated with longer pre‐transplant length of stay, and duration of hospitalization is a known risk factor to infection in both before and after liver transplant . However, pre‐transplant infection remained a significant risk factor for post‐transplant infection even when controlling for other confounding variables.…”
Section: Discussionmentioning
confidence: 91%
“…Statistical methods were in general poorly detailed, and mostly summarized in terms of descriptive statistics. Only three studies described the use of multivariate analysis -usually logistic regression -to control for confounding (45,147,168).…”
Section: Appraisal Of Risk Of Biasmentioning
confidence: 99%
“…The study design was clearly stated in 29 out of the 132 articles included ( Only one study reported sample size calculation and employed representative population although not powered for the prevalence detected nor for the comparison between the sub-groups performed (95). Measures of sampling variation in the results were reported by only four studies (95,161,165,168).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…Statistical methods were in general poorly detailed, and mostly summarized in terms of descriptive statistics. Only three studies described the use of multivariate analysis -usually logistic regressionto control for confounding (45,147,168). None of the studies took missing data into account in the analysis nor in the discussion, and similarly limitations and potential sources of bias were never mentioned in the discussion, with the exception of one surveillance study performed in Lebanon The cohort studies included in the review (52,131,161) showed overall lower risk of bias compared to other study designs.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%